Aprendizados com a diferença em uma experiência de paternidade: do testemunho ao cuidado - Pagni, Pedro Ângelo [UNESP] (My University, 2012)
This essay tells a singular experience of paternity, a parent's relationship to his daughter and learning of a child with special needs. This narrated experience has as an objective of the author's own narration of the transformations of this test, the theoretical features that marked his intellectual trajectory and limits them to express it. From this perspective, this essay seeks to give voice to this unique experience of caring with the goal of establishing a counterpoint with the discourse of inclusion and the specialized knowledge, with a view to a discursive event that produces a philosophical thinking and an apprenticeship with the difference that can promote the self-transformation of individuals who act in this field in their educational action.

Este ensaio narra uma experiência singular de paternidade, das relações de um pai com sua filha e do cuidado aprendido com uma criança com necessidades especiais. São narradas as próprias transformações do autor, usando os recursos teóricos que marcaram a sua trajetória intelectual e os limites dos mesmos para analisá-la. Estabelece-se um contraponto com o discurso da inclusão e dos saberes especializados, tendo em vista um acontecimento discursivo que produza um pensar filosófico e um aprendizado com a diferença capaz de promover a autotransformação dos sujeitos que atuam nesse campo em sua ação educativa.

Este ensayo narra una experiencia singular de paternidad,de las relaciones de un padre con su hija y delcuidado aprendido con un niño con necesidades especiales.Son narradas las propias transformaciones delautor, usando los recursos teóricos que marcaron sutrayectoria intelectual y los límites de los mismos paraanalizarla. Se establece un contrapunto con el discursode la inclusión y los saberes especializados, en la perspectivade un acontecimiento discursivo que produzcaun pensar filosófico y aprendizaje con la diferencia capazde promover la auto-transformación de los sujetos queactúan en ese campo en su acción educativa.Palabras claveExperiencia, diferencia, cuidado, testimonio.
Learning with a difference in an experience of paternity: from testimony to caring
Keywords: Experiência; cuidado de si; Filosofia da diferença